Prospecting the roles of Trichoderma in sustainable crop production: biotechnological developments and future prospects - Rizky Riscahya Pratama Syamsuri; Dwi Astuti Aprilia; Atasya Yasmine Fakhira; Almira Salma Nabilah; Sulistya Ika Akbari; Nia Rossiana; Febri Doni (UNIVERSITAS NEGERI PADANG, 2022)
The filamentous fungal genus Trichoderma are reported to have a significant impact on the growth and development of various crops. Trichoderma species which are residing in the rhizosphere of crops, and as fungal symbionts living within plant tissues have multiple roles in enhancing crops’ agronomic traits, fitness, growth and yield, and in modulating their tolerance towards biotic and abiotic stresses. This article discusses on the potential and impact of Trichoderma in improving the development and production of crops, as well the mechanism of Trichoderma in improving the development and production of crops. This article also highlights the ability of Trichoderma for improving crops’ tolerance to abiotic and biotic stresses. Prospectively, the use of Trichoderma inoculants offers some new, cost-effective, and more eco-friendly practices for increasing crops’ production.